2021
DOI: 10.1007/s00405-021-06916-0
|View full text |Cite
|
Sign up to set email alerts
|

Observational study investigating Ectoin® Rhinitis Nasal Spray as natural treatment option of acute rhinosinusitis compared to treatment with Xylometazoline

Abstract: Introduction Symptomatic relief of acute rhinosinusitis is commonly achieved with nasal decongestants. The current observational study investigated the efficacy and safety of treatment of acute rhinosinusitis with Ectoin® Rhinitis Spray compared to or in combination with Xylometazoline-containing decongesting nasal spray. Methods Patients with acute rhinosinusitis applied either Ectoin® Rhinitis Spray, Xylometazoline nasal spray or a combination of both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In addition, ectoine protects the ileal mucosa from ischemia-reperfusion injury, a common complication after small bowel transplantation [ 32 ]. Several recent studies reported that ectoine-containing sprays effectively treat acute pharyngitis, allergic rhinitis, and rhinoconjunctivitis [ 33 , 34 ]. However, the effects of ectoine on OA treatment have not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ectoine protects the ileal mucosa from ischemia-reperfusion injury, a common complication after small bowel transplantation [ 32 ]. Several recent studies reported that ectoine-containing sprays effectively treat acute pharyngitis, allergic rhinitis, and rhinoconjunctivitis [ 33 , 34 ]. However, the effects of ectoine on OA treatment have not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported that ectoine-containing sprays effectively treat acute pharyngitis, allergic rhinitis, and rhinoconjunctivitis [33,34]. However, the effects of ectoine on OA treatment have not been reported to date.…”
Section: Plos Onementioning
confidence: 99%
“…The majority of doctors in this study reported that the use of xylometazoline with sorbitol and hypromellose also eases nasal dryness. This property of the formulation is beneficial because dryness of the nasal mucosa can lead to pain and nosebleeds, increasing the burden on patients [8]. Therefore, it can be concluded that xylometazoline with sorbitol and hypromellose is an effective treatment for nasal congestion that also relieves nasal dryness.…”
Section: Discussionmentioning
confidence: 99%
“…Xylometazoline hydrochloride is a well-established topical nasal decongestant. This sympathomimetic drug acts selectively on α-adrenergic receptors (alpha-adrenergic agonist) [8]. Patients report relief from nasal congestion within 2 minutes of use of xylometazoline, and the increase in nasal conductance is five times higher than that noted with oral decongestants [9].…”
Section: Introductionmentioning
confidence: 99%